Empowering Coconut Coir Waste through COCONET Innovation for Post-Mining Reclamation: A CSR Initiative by PT ANTAM Tbk. UBPN North Maluku - Agustinus Toko Susetio; Arisyono; Fredy Utama; Yacob Sampe; Krisno Budiharto (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
The COCONET development program represents an innovative approach to post-mining land reclamation based on the utilization of coconut coir waste. Developed by PT ANTAM Tbk, North Maluku Nickel Mining Business Unit (UBP), this program targets not only ecological restoration but also the social and economic empowerment of local communities through an inclusive empowerment scheme. This article systematically examines the design, implementation, and impact of the COCONET program from environmental, social, and economic perspectives, while also assessing its potential for replication in other regions. This study adopts a descriptive-qualitative method using a case study approach. The findings reveal that the COCONET program has successfully established an efficient, environmentally friendly, and inclusive reclamation model.